2010
DOI: 10.1161/circulationaha.109.878389
|View full text |Cite
|
Sign up to set email alerts
|

Defi 2005

Abstract: Following prompts from AEDs programmed with a protocol similar to Guidelines 2005, firefighters shortened pauses in CPR and improved overall hands-on time, but survival to hospital admission of patients with ventricular fibrillation out-of-hospital cardiac arrest did not improve. Clinical Trial Registration- http://www.clinicaltrials.gov. Unique identifier: NCT00139542.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 35 publications
1
41
0
2
Order By: Relevance
“…This finding is consistent with other reports. In 845 OHCA patients randomized to 2 protocols, Jost et al 21 reported a substantial difference in preshock pause duration (9 versus 19 seconds) but no difference in VF termination between groups. In 223 OHCA patients, Kramer-Johansen et al 6 compared defibrillation using manual and AED mode and found a significant difference in preshock pause duration (15 versus 22 seconds) but no difference in VF termination rate (61% versus 60%), despite a higher rate of postshock pulse-generating rhythms in the manual defibrillation arm (7% versus 3%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other reports. In 845 OHCA patients randomized to 2 protocols, Jost et al 21 reported a substantial difference in preshock pause duration (9 versus 19 seconds) but no difference in VF termination between groups. In 223 OHCA patients, Kramer-Johansen et al 6 compared defibrillation using manual and AED mode and found a significant difference in preshock pause duration (15 versus 22 seconds) but no difference in VF termination rate (61% versus 60%), despite a higher rate of postshock pulse-generating rhythms in the manual defibrillation arm (7% versus 3%).…”
Section: Discussionmentioning
confidence: 99%
“…23 The Paris emergency medical system is a 2-tiered response system coordinated via a unique dispatcher center: a basic life support tier provided by firefighters of the Brigade de Sapeurs Pompiers de Paris, who can apply an AED, and an advanced cardiac life support function provided by ambulance teams with an emergency physician, a nurse, and a paramedic (Service d'Aide Médicale Urgente).…”
Section: Population Studymentioning
confidence: 99%
“…Recent evidence shows that there is no difference in VF recurrence or outcome in terms of survival between the two strategies. (15,16) As in the 2011 National Resuscitation Council guidelines, a single shock followed by CPR is favoured over the three-stacked shock strategy (17) for persistent VF. With biphasic machines, the termination rate of VF is very high.…”
Section: Management Of Persistent Vfmentioning
confidence: 99%